Postoperative neck pain associated with an implantable microvascular ultrasonic Doppler: a case report. Issue 3 (April 2019) - Huston, M.; Merrick, G.; Al-Rikabi, A.
Abstract: Microvascular reconstruction in the head and neck has enabled the transfer of large amounts of tissue, and has improved functional and cosmetic outcomes for patients. Its success is primarily dependent on adequate perfusion, and though many methods have been used to monitor the circulation of flaps, the Cook-Swartz implantable Doppler has gained favour with surgeons and nursing staff. We present the unusual case of a patient who had developed recurrent infection and pain that was associated with its use.